Environmental indicators of lake ecosystem health in Aotearoa New Zealand: current state and trends - Anika Kuczynski; Rachel G.R. Smith; Caroline E. Fraser; Scott T. Larned (Ecological Indicators, 2024)
Assessments of lake ecosystem health, based on indicators of physical–chemical water quality, ecological conditions, and human health risks, are needed to apprise the public and facilitate lake management. While unrefereed lake water quality reports exist, this is the first peer-reviewed study to report data processing and analysis methods and results for current state and recent trends in multiple environmental indicators in monitored lakes across Aotearoa New Zealand. Lake grading based on national criteria indicated that many lakes are failing to achieve statutory bottom lines for phytoplankton chlorophyll a, total nitrogen, and total phosphorus concentrations. In contrast, most monitored lakes had high grades for two human health risk indicators, E. coli and cyanobacteria concentrations, and for potential toxicity of ammonia for biological communities. We included 166 lakes and considered indicator state and trends for two lake classifications based on geomorphology and land cover. Elevated scores for an indicator of trophic state (the trophic level index; TLI) in most shoreline, riverine, peat, landslide, dam, and aeolian lakes indicated eutrophic conditions or worse. Lower TLI scores were indicative of oligotrophic conditions in most glacial lakes. Nutrient, E. coli and suspended sediment concentrations and TLI scores were positively correlated, and Secchi depths negatively correlated, with high-intensity agricultural land cover. Ten-year trend analyses indicated that lakes with increasing Secchi disk depth, chlorophyll a, dissolved reactive phosphorus, E. coli, ammoniacal nitrogen, TLI, total nitrogen, and total suspended solids trends outnumbered those with decreasing trends. Twenty-year trend analyses indicated that the numbers of lakes with increasing and decreasing trends in most of the indicators we assessed were comparable, but lakes with increasing 20-year trends in total nitrogen outnumbered those with decreasing trends, and lakes with decreasing 20-year trends in ammoniacal nitrogen, dissolved reactive phosphorus, total phosphorus, and nitrate nitrogen outnumbered those with increasing trends. This study presents clear data processing steps and trend analysis methods as applied to a nationwide dataset for Aotearoa New Zealand, while acknowledging data limitations. For example, the choice of trend periods is challenging and can greatly affect conclusions. The results of this empirical study and the collective results of preceding studies of lake ecosystem health indicate that eutrophication poses a threat to the ecological health of many if not most lakes in Aotearoa New Zealand. Recommendations include monitoring network expansion especially for the indicators bottom dissolved oxygen and cyanobacteria (toxic and total cyanobacteria biovolumes) and judicious selection of trend periods in lake-specific trend analyses to determine causes for increasing or decreasing trends in environmental indicators.